Pretextual Fourth Amendment Activity: Another Viewpoint - Haddad, James B. (1985)
Pretextual detentions, arrests, and searches pose knotty fourth amendment problems. With an air of plausibility, defense attorneys often accuse police of pretextual use of arrest warrants, search warrants, and various exceptions to the warrant requirement. Specifically, they contend that officers have utilized a particular fourth amendment doctrine to obtain certain evidence even though courts have not assigned as a reason for approving the doctrine the need to discover such evidence